2018
DOI: 10.1002/aet2.10096
|View full text |Cite
|
Sign up to set email alerts
|

The Intersection of Gender and Resuscitation Leadership Experience in Emergency Medicine Residents: A Qualitative Study

Abstract: Residents acknowledged that additional challenges exist for female residents in becoming resuscitation team leaders. Increasing awareness in residency program leadership is key to affecting change to ensure all residents are trained in a similar manner, while also addressing gender-specific needs of residents where appropriate. We present suggestions for addressing these barriers and incorporating discussion of leadership styles into residency training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 17 publications
4
28
0
Order By: Relevance
“…With respect to when medical residents negotiate (negotiation frequency), it became apparent that medical residents interacted more with nurses than with their supervisors. Nurses expect female medical residents to be more sympathetic and communicative as described by Linden et al 20 This could explain why medical residents interact more often with nurses than with supervisors to build trust and a good relationship 20 - 22 . Even though medical residents interacted more frequently with nurses, negotiation frequency did not vary with WE, hierarchy, NS, NK or CS.…”
Section: Discussionmentioning
confidence: 87%
“…With respect to when medical residents negotiate (negotiation frequency), it became apparent that medical residents interacted more with nurses than with their supervisors. Nurses expect female medical residents to be more sympathetic and communicative as described by Linden et al 20 This could explain why medical residents interact more often with nurses than with supervisors to build trust and a good relationship 20 - 22 . Even though medical residents interacted more frequently with nurses, negotiation frequency did not vary with WE, hierarchy, NS, NK or CS.…”
Section: Discussionmentioning
confidence: 87%
“…Narrative analysis of the included studies collectively indicates that there are two types of leadership in ED. The first type relates to clinical leadership, which involve leading a team to complete specific clinical tasks, such as trauma management or resuscitation 11–13,20–33 . This may be performed by the attending fellow or resident physician who may or may not have a formal leadership position but who does have the necessary clinical expertise.…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with this, the literature provided important insights into the dynamic delegation of leadership 27 and the interplay between directive, facilitative and shared leadership styles in ad hoc interdisciplinary extreme action teams. 15,29,32 This line of inquiry draws attention to the notion that leadership in ED teams is characterised not by a single leadership style by a formal leader, but rather a range of styles that are deployed dynamically, formally and informally by a range of actors as a function of a range of situational and social factors. This suggests that ED team leadership is pluralistic, relational, dynamic and contingent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have attempted to explore the dynamic relationships between genders in leadership positions in medicine. Keck‐McNulty and Wear reported that female residents most commonly expressed “excessive self‐monitoring of communication style due to fears of being perceived as too demanding and not friendly enough … having to justify their orders more than their male peers … and receiving less assistance than their male peers.” The study of female leadership roles during resuscitations by Linden and colleagues also revealed gender discrepancies, stating that “female residents had to earn the trust and respect of the nurses more than their male counterparts.” These prior studies suggest that female residents continue to face challenges in their training program that their male counterparts do not.…”
mentioning
confidence: 99%